2017
DOI: 10.28932/jmm.v16i2.388
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Tingkat Edukasi dan Spesialisasi Pendidikan CEO terhadap Performa Perusahaan di Indonesia

Abstract: Nilai perusahaan ditetapkan melalui kinerja manajemen dan kinerja keuangan perusahaan. Kinerja keuangan dapat diukur dengan beberapa pendekatan rasio keuangan, baik likuiditas, profitabilitas, solvabilitas, aktivitas maupun rasio pasar. Kebijakan dan keputusan para investor dalam menginvestasikan modelnya ke dalam perusahaan lebih dipengaruhi oleh rasio profitabilitas yang dimiliki oleh suatu perusahaan dibandingkan dengan rasio lainnya. Hal ini dikarenakan investor menganggap bahwa rasio profitabilitas dapat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
1
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 7 publications
0
11
1
5
Order By: Relevance
“…Every firm needs professional directors whose expert in their fields, they must have a specific formal education background and have experience in working according to their expertise because the skills required to make managerial decisions are not always formed only from formal education qualifications [9]. In Indonesia, education levels and specialization have been shown to have a positive influence on performance and are used as the company's primary consideration in selecting CEOs [11].…”
Section: Introductionmentioning
confidence: 99%
“…Every firm needs professional directors whose expert in their fields, they must have a specific formal education background and have experience in working according to their expertise because the skills required to make managerial decisions are not always formed only from formal education qualifications [9]. In Indonesia, education levels and specialization have been shown to have a positive influence on performance and are used as the company's primary consideration in selecting CEOs [11].…”
Section: Introductionmentioning
confidence: 99%
“…From the differences in the theory of Wulf and Stubner (2013); Erlim and Juliana (2017) and several previous research results, the authors see that the level of education and specialization of President Director does not have a direct effect on company performance but may affect the mindset of the President Director in making decisions. Also, there is a research gap conducted by Singla (2020), which concludes that VAIC and other components do not affect company ROA, thus allowing the emergence of other factors that can strengthen to prove the effect of intellectual capital on company performance.…”
Section: Introductionmentioning
confidence: 71%
“…Several previous studies by Erlim and Juliana (2017); Setiawan and Gestianti (2018); Saidu (2019); Tullah (2017) stated that there was a significant positive effect on the level of education of the President Director on company performance.…”
Section: Effect Of Intellectual Capital On Firm Performance With Pres...mentioning
confidence: 87%
See 1 more Smart Citation
“…Some studies found that CEOs with post-graduate education tend to lessen the firm's performance, due to the overconfidence of bias and too much R & D activity [25], [13], [1]in his study using fractional logistic regression found that R&D activity can reduce the value of foreign investment in the company. Conversely, one study found that firms with high CEO education levels have a positive Table 1: Variable specification impression on the stock market that creating abnormal returns [26]In addition, other study found that there is a positive influence of CEOs who have degrees from a prestigious university and CEO with MBA degrees on a firm's financial performance [12] and therefore attract more foreign investment [1] Therefore, the hypothesis is proposed as follows:…”
Section: Literature Reviewmentioning
confidence: 99%